Two new species and a new record of Comesomatidae (Nematoda, Araeolaimida) from Southern Hikurangi Margin, New Zealand - Rosli, Norliana; Leduc, Daniel; Probert, P. Keith (Zootaxa, 2014)
We describe two new species and provide one new species record of the family Comesomatidae from a submarine canyon habitat on the Southern Hikurangi margin, New Zealand. Vasostoma hexodontium n. sp. is characterized by having an amphideal fovea with three turns, buccal cavity with six teeth and gubernaculum with long and straight caudal apophyses. Sabatieria dispunctata n. sp. is characterized by the absence of cuticle punctations, large amphideal fovea with 4.5 turns, pharynx with posterior bulb, absence of pre-cloacal supplements, strongly arcuate and cuticularized spicules, simple gubernaculum with short caudal apophyses, and vulva opening directed posteriorly. Laimella subterminata Chen & Vincx, 2000, which was originally described from the Beagle Channel and the Magellan Strait (Chile), is recorded from the Southwest Pacific for the first time.